Aerosol-orography-precipitation – A critical assessment. (1st October 2019) - Choudhury, Goutam; Tyagi, Bhishma; Singh, Jyotsna; Sarangi, Chandan; Tripathi, S.N.
Abstract: The increasing anthropogenic pollution and its interaction with precipitation received much attention from the research community and have been explored extensively for understanding the aerosol-cloud interactions. The impacts of orography and aerosols on the precipitation processes have unveiled the Aerosol-Orography-Precipitation (AOP) interaction as an essential research area. The understanding of AOP interaction is critical for improving the extreme rainfall events prediction over mountainous regions. The phase of clouds (warm or mixed) along with orography has emerged as a significant factor for influencing the AOP relations. The present work reviews the modelling and observational based studies dealing with the relationship between orography and aerosols on the precipitation. The study reveals the principal role of aerosols in shifting the precipitation pattern for orographic regions. The environmental factors, especially ambient temperature, humidity and flow patterns are also identified to affect the orographic precipitation. The review also discovers that AOP studies exist only to limited areas of the world due to limited observations, and mostly with idealised cases in the modelling framework. Graphical abstract: Image 1 Highlights: The study reviews Aerosol-orography-precipitation interactions. The present study takes in to account both observational and modelling studies. The study classifies the role of Aerosols to orography-precipitation interaction. The different regions of the world with no such research have been identified.